2013
DOI: 10.1371/journal.pone.0066224
|View full text |Cite
|
Sign up to set email alerts
|

An Appended Domain Results in an Unusual Architecture for Malaria Parasite Tryptophanyl-tRNA Synthetase

Abstract: Specific activation of amino acids by aminoacyl-tRNA synthetases (aaRSs) is essential for maintaining fidelity during protein translation. Here, we present crystal structure of malaria parasite Plasmodium falciparum tryptophanyl-tRNA synthetase (Pf-WRS) catalytic domain (AAD) at 2.6 Å resolution in complex with L-tryptophan. Confocal microscopy-based localization data suggest cytoplasmic residency of this protein. Pf-WRS has an unusual N-terminal extension of AlaX-like domain (AXD) along with linker regions wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The 36-member P. falciparum parasite tRNA synthetase family, which together governs transmission of genetic information into proteins, has been focus of intense research lately (Bhatt et al, 2009(Bhatt et al, , 2011Istvan et al, 2011;Jackson et al, 2011;Jain et al, 2014;Khan et al, 2011Khan et al, , 2013aKhan et al, , 2013bKhan et al, , 2014Koh et al, 2012;Pham et al, 2014). The recent discovery and validation of cladosporin utility against multiple malaria parasitic stages, and its specificity for PfKRS, has been a seminal contribution in validating aaRSs as new drug targets (Hoepfner et al, 2012;Khan et al, 2013aKhan et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 36-member P. falciparum parasite tRNA synthetase family, which together governs transmission of genetic information into proteins, has been focus of intense research lately (Bhatt et al, 2009(Bhatt et al, , 2011Istvan et al, 2011;Jackson et al, 2011;Jain et al, 2014;Khan et al, 2011Khan et al, , 2013aKhan et al, , 2013bKhan et al, , 2014Koh et al, 2012;Pham et al, 2014). The recent discovery and validation of cladosporin utility against multiple malaria parasitic stages, and its specificity for PfKRS, has been a seminal contribution in validating aaRSs as new drug targets (Hoepfner et al, 2012;Khan et al, 2013aKhan et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, several groups have been investigating the structure-function attributes of aaRSs within malaria parasites (Bhatt et al, 2009(Bhatt et al, , 2011Istvan et al, 2011;Jackson et al, 2011;Jain et al, 2014;Khan et al, 2011Khan et al, , 2013aKhan et al, , 2013bKhan et al, , 2014Koh et al, 2012;Pham et al, 2014). Targeting parasitic aaRSs can provide an additional drug component in current multidrug anti-malarial therapy (Bhatt et al, 2009(Bhatt et al, , 2011Hoepfner et al, 2012;Istvan et al, 2011;Jackson et al, 2011;Jain et al, 2014;Khan et al, 2011Khan et al, , 2013aKhan et al, , 2013bKhan et al, , 2014Koh et al, 2012;Pham et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Aminoacyl-tRNA synthetases (aaRSs) are ubiquitous enzymes that attach amino acids onto cognate tRNAs that eventually feed into protein translation [1]. The structure-function attributes of parasitic aaRSs have been under intense investigation lately [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and of 36 Plasmodium falciparum aaRSs several have been proposed as drug targets [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The present enzyme in discussion-V. Jain Á A. Sharma Á M. Yogavel (&) Structural and Computational Biology Group, International Centre for Genetic Engineering and Biotechnology (ICGEB), New Delhi 110067, India e-mail: myogavel@yahoo.com prolyl-tRNA synthetase (PRS) is the latest in this regard [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…One early study reported aaRS activity in P. berghei cell-free extracts (89), and genome sequencing later revealed the entire complement of aaRSs in Plasmodium (10,68,88). But to date, cytoplasmic and apicoplast P. falciparum aspartyl-tRNA synthetase (28,29), lysyltRNA synthetase (30,31), and tryptophanyl-tRNA synthetase (32,33) are the only other malarial aaRSs besides PfGluRS to be functionally or structurally characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Mupirocin, for example, is a topical antibiotic already in clinical use, and other aaRS inhibitors such as the boronated antifungal compound AN2690 (27) are being developed. Aminoacylation in malaria parasites had been little studied despite its critical role in parasite biology and potential as a drug target, but studies describing the apicoplast (28) and cytoplasmic aspartyl-tRNA synthetases (29), lysyl-tRNA synthetases (30,31), and tryptophanyl-tRNA synthetases (32,33) were recently published.…”
mentioning
confidence: 99%